Enhancing Reading Instruction for Second Semester Students at Universitas Nahdlatul Ulama Sidoarjo Using Graphic Organizers - Ryan Purnomo; Evi Mavidhotul Ilmi; Tri Septianto (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
The aim of this research is to describe the process, advantages, and disadvantages of implementing Graphic Organizers (GO) in teaching reading. This study is of a descriptive qualitative nature and was conducted in the English Teaching Department of Universitas Nahdlatul Ulama Sidoarjo. Class PBI 2021 was selected as the sample using the purposive sampling technique. Data collection was carried out through observation and interview methods. Data analysis involved the steps of data classification, interpretation, and conclusion. The results of this research indicate that the application of GO consists of three steps: pre-reading, while reading, and post-reading. The advantages include making reading instruction more effective, fostering cooperative learning environments, enhancing students' confidence and motivation in reading classes, and promoting an active and engaging classroom atmosphere. However, some disadvantages were noted, such as the strategy's limited applicability to certain texts and the potential for increased noise levels in the classroom. It is recommended for lecturers to incorporate this strategy into their reading instruction.